The Body in Mind: Mead's Embodied Cognition. Issue 3 (12th January 2020) - McVeigh, Ryan
Abstract : This article highlights the role played by the body in the work of George Herbert Mead. For Mead, the social emergence of mind depends on human physiology. This is revealed through a detailed exploration of three thematic domains in his work: the organism–environment dyad, perception, and the manipulatory stage of the act. From this, I argue that Mead saw the body as constitutive of cognition and central to the development of mind and self. Present‐day research supports this view and demonstrates Mead's relevance for understanding embodied cognition.